The Effect Of The Exchange Rate On Demand For Money In Sudan: The Question Of Asymmetry - Sayed, Dr Omer Ahmed (The journal of contemporary issues in business and government, 2021)
In this study, we intended to examine the asymmetric effect of exchange rates on demand for money in Sudan. Applying the Non-linear ARDL model to annual data for the period 1960 to 2019, using inflation, real GDP, and profit margin of Murabaha as control variables. Few studies found that test the non-linearity effect of the exchange rate on money demand in Sudan. This paper tried to fill this gap by testing the impact of the Sudanese Pound exchange rate non-linearity on the money demand in Sudan. The findings show that asymmetric effect of the exchange rate on money demand both the short run as well as long run were found. The policy implication of our results is that assuming a symmetry relationship between the exchange rate and demand for money may affect the economic planning negatively. Thus, non-linear ARDL assumes to be more suitable than the linear ARDL for examining such a relationship.